Section 2.7 Question 50 [ATTACH=full]558[/ATTACH] (x^2 + x - 6)/x ≥ 0 Immediately I see that x cannot be zero. To show this fact, we draw a hole on the real number line at x = 0. Factoring the numerator, I get (x - 2)(x + 3). Setting to zero, I get x = 2 and x = -3. See number line below. When x = -4, we get -3/2 ≥ 0. False statement. When x = -3, we get 0 ≥ 0. True statement. The hole is filled at x = -3. When x = -2, we get 2 ≥ 0. True statement. When x = 1, we get -4 ≥ 0. False statement. When x = 2, we get 0 ≥ 0. True statement. The hole is filled at x = 2. When x = 3, we get 2 ≥ 0. The following intervals satisfy the original inequality: [-3, 0) U (0, -2] U [2, infinity) [ATTACH=full]559[/ATTACH]